THE PHENOMENON OF FOOD WASTE IN BREAKFAST BUFFET SERVICES FOR SUSTAINABLE TOURISM - Herryani , Herra; Sony Heru Priyanto; Nur Widiyanto; Yuliyanto Nugroho, Agung; Ristanti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Food waste in buffet services in the tourism sector is a strategic issue that has significant impacts on environmental, economic, and social aspects, especially in the context of efforts to achieve sustainable tourism. This study aims to analyze in-depth strategies for preventing food waste in buffet services by highlighting operational practices, guest behavior, and managerial policies implemented in the field. The research approach uses qualitative methods with data collection techniques through direct observation, in-depth interviews with hotel managers and staff, and documentation studies related to the food production and serving processes. The research results indicate that the most effective food waste prevention strategies include ongoing guest education on responsible consumption behavior, the implementation of flexible and adaptive portion sizes tailored to guest needs, and staff capacity building through training on food management and waste mitigation. Furthermore, strengthening coordination between the kitchen, restaurant service, and management is also crucial in ensuring optimal strategy implementation. These findings provide practical and academic contributions to the tourism industry by offering recommendations that can serve as a basis for developing more efficient and sustainable policies and operational practices, thereby reducing the negative impact of food waste while improving the quality of buffet service.